Human Resources Education and Innovation to face the demands of Business in the Digital Age - Eric Hermawan; Antoni Ludfi Arifin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
This article discussed the importance of education and human resource (HR) innovation in dealing with business demands in the digital era. Human resources meet business demands through education and innovation to achieve profit and business sustainability goals. Therefore, we have conducted a series of data searches and analyses to answer this paper's core discussion. This research was carried out on several data findings from literature sources of well-known journal publications such as Google Book, Google Scholar, Taylor & France, Elsevier, and other publications that discuss issues of strengthening human business resources towards the era of technology. To get answers to the problems of this study, we involve a coding system, data interpretation, and high-level evaluation to get valid and reliable data. Based on the findings and discussion data, this result show that the importance of education and innovation in increasing the capacity of human business resources was dynamic and adaptable to the demands of the high-tech business era. Thus, this finding answer the search for business HR solutions and become a meaningful input for future business study efforts. Keywords: Innovation Education, Human Resource Education, Digital Age